Comparison of SAPIEN 3 and SAPIEN XT transcatheter heart valve stent-frame expansion: evaluation using multi-slice computed tomography. (21st March 2016) - Kazuno, Yoshio; Maeno, Yoshio; Kawamori, Hiroyuki; Takahashi, Nobuyuki; Abramowitz, Yigal; Babak, Hariri; Kashif, Mohammad; Chakravarty, Tarun; Nakamura, Mamoo; Cheng, Wen; Friedman, John; Berman, Daniel; et al.
Abstract: Aims: Stent-frame morphology of the newer-generation, balloon-expandable transcatheter heart valve (THV), the SAPIEN 3 (S3), after transcatheter aortic valve implantation (TAVI) is unknown. We evaluated the THV stent-frame morphology post TAVI of the S3 using multi-slice computed tomography (MSCT) compared with the prior-generation THV, SAPIEN XT (S-XT). Methods and results: A total of 94 consecutive participants of RESOLVE registry (NCT02318342) had MSCT after balloon-expandable TAVI (S3 = 39 and S-XT = 55). The morphology of the THV stent-frame was evaluated for expansion area and eccentricity at the THV-inflow, native annulus, mid-THV and THV-outflow levels. Mean %-expansion area for the S3 and the S-XT was 100.9 ± 5.7 and 96.1 ± 5.5%, respectively ( P < 0.001). In the S3 group, the THV-inflow level had the largest value of %-expansion area, which decreased from THV-inflow to mid-THV level (105.2 ± 6.4 to 96.5 ± 5.9%, P < 0.001). However, in the S-XT group, %-expansion area increased from THV-inflow level to mid-THV level (93.2 ± 6.2 to 95.1 ± 6.1%, P = 0.0058). On nominal delivery balloon volume, the S3 in 88.5% of cases had overexpansion at the THV-inflow level. The observed degree of THV oversizing of the S3 was significantly lower than the S-XT (6.3 ± 8.6 vs. 11.8 ± 8.5%, P = 0.0027). Nonetheless, the incidence of post-procedural paravalvular aortic regurgitation (PVR) ≥ mild following the S3 TAVI was also significantly lower than the S-XT TAVI (17.9 vs. 43.6%, P = 0.014). Conclusion: The newer-generation, balloon-expandable device, the S3, has a flared inflow morphology, whereas the prior-generation device, the S-XT, has relatively constrained inflow morphology post TAVI. This may contribute to a lesser degree of PVR with the S3.